The Needs of English Teacher in Handling Technology for Online Classes - Jovanka Nabila; Arrasyid, Farouk Imam; Noerjanah, Siti Luruh Ayu (EDUCAFL: Journal on Education of English as Foreign Language, 2024)
The main problem this study identified is that English language teachers continue to teach English in an environment of outdated technology. Teachers need to improve their proficiency in information and communication technology and English in addition to becoming proficient in English because virtually all 21st-century institutions are using online classes. Duty to set a good example for kids so they can accomplish their learning goals. The aim of this research is to investigate the constraints imposed on English teachers concerning their capacity to employ technology efficiently in virtual learning settings. This research uses qualitative methods in addition to a case study approach. In order to collect data, researchers used observation, interviews, and documentation. In order to locate research participants, purposeful sampling was employed. As a result of their extensive experience with technology, junior high school English teachers are well-suited to teach online. Pedagogical, personal, professional, and social skills have been highlighted as the most important attributes for English teachers to master. English teachers should focus on six main areas while developing their pedagogical competencies for online teaching. To improve personality competence in online English lessons, English teachers should concentrate on five main areas. English teachers should concentrate on three main areas in order to develop professional and social competence for their online students. When teaching online, English teachers in schools are utilized to handling technology.